Classical Photoreceptors Regulate Melanopsin mRNA Levels in the Rat Retina - Sakamoto, Katsuhiko (J Neurosci, 2004)
Recent studies have demonstrated that melanopsin is a key photopigment in the mammalian circadian system. This novel opsin is exclusively expressed in retinal ganglion cells that are intrinsically sensitive to light, perhaps responding via a melanopsin-based signaling pathway. Previous investigations using transgenic mice have also demonstrated that ablation of the classical photoreceptors and of melanopsin prevents entrainment of several circadian rhythms, thus demonstrating that these photoreceptors are necessary and sufficient for circadian photoreception. In this study, we investigated the effect of photoreceptor degeneration on melanopsin mRNA regulation in RCS/N-rdy rats (Royal College of Surgeons rats with a defect in the retinal dystrophy gene). We used animals at postnatal day 21 (P21), P33, P45, and P60. At P60 degeneration of the retina in RCS/N-rdy has advanced to the point where the majority of the photoreceptors have degenerated. Our data indicate that melanopsin mRNA levels were rhythmic in light/dark cycle and in constant darkness in congenic controls (RCS/N-rdy(+)) and in RCS/N-rdy at P21 (i.e., before the degeneration of the photoreceptors). On the other hand, in RCS/N-rdy at P60, melanopsin mRNA levels were greatly reduced (<90%) and not rhythmic. Photoreceptor degeneration did not affect the expression of pituitary adenylate cyclase-activating polypeptide mRNA (a marker for melanopsin-containing ganglion cells). Our results suggest that classical photoreceptors (rods and cones) regulate the expression of melanopsin mRNA in the rat. Because RCS/N-rdy rats are a model for studies on retinitis pigmentosa in human, our data may provide an important insight on melanopsin function in patients affected by retinitis pigmentosa.